(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The primary motive behind this the present investigation was to develop and optimize the solid lipid nanoparticles formulation of candesartan to enhance solubility and dissolution rate. The prepared SLNs, composed of precirol, poloxamer 188, soy lecithin, tween 80, were fabricated employing hot emulsification/ ultrasonication technique. Box-Behnken design was employed for 17 formulation batches in which 3 factors namely lipid, surfactant, and co-surfactant (precirol, poloxamer 188 and soy lecithin) tween 80 were tested at 3 levels of their concentration, i.e., low, medium and high. The effect of different levels of factors was evaluated for the particle size, entrapment efficiency and % cumulative drug release. Kinetic model fitting for candesartan solid lipid nanoparticles (SLN) formulation was done to interpret the release rate from the SLN. Optimized formulation was subjected for fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM) and stability studies. The mean particle size, PDI, zeta potential, entrapment efficiency, content uniformity and in-vitro drug release of optimized candesartan-loaded SLNs (CD10) were found to be 135.38 ± 3.41 nm, 0.125 ± 0.04, -18.16 ± 2.89 mV, 86.4 ± 2.35%, 99.78 ± 2.54% and 98.91 ± 0.85% respectively. The release kinetics suggested that drug release followed zero-order and release was anomalous non-fickian diffusion super case II transport. FTIR studies revealed no incompatibility between drug and excipients, SEM images exhibited nanoparticles to be more porous and in a spherical shape. Stability studies indicated good stability of the formulation. The proposed way of SLN preparation could be considered a proper method for producing a candesartan-loaded colloidal carrier system.